Pengaruh Besaran Pajak, Pendapatan Wajib Pajak, Pengetahuan Perpajakan dan Kemudahan Akses terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Solo - Widya Ardhini Kusumaningtyas; Rukmini; Wikan Budi Utami (Nur Science Institute, 2026)
This study examines the effects of tax amount, taxpayer income, tax knowledge, and ease of access on motor vehicle taxpayer compliance in Surakarta City. A quantitative approach with an associative research design was employed. Primary data were collected through questionnaires from 100 taxpayers selected using an accidental sampling technique and analyzed using multiple linear regression with IBM SPSS Statistics 27. The results indicate that tax knowledge and ease of access have a positive and significant effect on taxpayer compliance, whereas tax amount and taxpayer income have no significant effect. Simultaneously, all independent variables significantly influence taxpayer compliance with a coefficient of determination (R²) of 0.502. These findings suggest that improving taxpayer compliance depends more on strengthening tax knowledge and enhancing access to tax services than on economic factors. Therefore, local governments should improve tax education and the quality of tax payment services.